Does the Intra-operatively measured Leg Length Correction compare to the Post-operative radiograph in Total Hip Replacement surgery? - Moonda, Zaheer (Division of General Surgery, 2021)
Aims This study aims to compare the leg length correction (LLC) measured intra-operatively using the Vertical Measurement SystemTM (VMS) in total hip arthroplasty (THA), with the LLC measured on a 6-week post-operative Xray. We also wanted to quantify any residual leg length discrepancy (LLD) using this method. Patients and Methods A prospective cohort study was conducted, in which patients undergoing primary THA were enrolled at two centres in Cape Town, over a period of 19 weeks. THA's were performed by four surgeons. Pre-operative leg length discrepancy measurements were obtained in 92 patients. The VMS was used to predict intra-operative leg length correction (LLC), and this measurement was compared to the post-operative leg length correction measured on the 6-week follow-up X-ray. These measurements were statistically compared using Mann-Whitney U Test. Results The difference between the intra-operative VMS calculation and the 6-week radiological measurement was not significant (p>0.05), with the difference in their mean values being 0.07 ± 3.26mm. In the cohort, 81.52% of the patients (n=75) were within 5mm of the target LLC, and 95.65% of patients (n=88) were within 10mm of the target LLC. The mean absolute residual LLD at 6 weeks was 3.22 ± 3.13mm. Conclusion The intra operative LLC measurement obtained using the VMS accurately predicts the 6-week post op radiographic LLC measurement.